Aging of Aglianico and Sangiovese wine on mannoproteins: Effect on astringency and colour. (May 2019) - Rinaldi, Alessandra; Coppola, Marianna; Moio, Luigi
Abstract: During the last years different commercial preparations based on yeast derivatives have been used in order to replace traditional ageing on lees. Three commercial mannoproteins (MP; MF; MS) were tested in Aglianico and Sangiovese red wine during one year of aging to evaluate the influence on astringency characteristics (astringency intensity and 16 subqualities), colour parameters (CIE L*a*b* coordinates, total anthocyanins, pigmented polymers) and reactive phenolic compounds (BSA-reactive tannins, saliva-reactive tannins, vanillin reactive flavans) after 3, 6 and 12 months. The taste, odor and aroma profiles completed the sensory evaluation of one-year aged wines. The effect of commercial mannoproteins on studied parameters depended on wine variety and aging period. As regard wine colour evolution, the formation of pigmented polymers was promoted from the 6th month in Aglianico by MS and MF, and in Sangiovese by all mannoproteins. Regarding wine sensory evaluation, MP reduced the astringency of Aglianico and enhanced the positive subqualities, while all mannoproteins favored spicy and balsamic notes revelation. In Sangiovese, green tannins and herbaceous notes decreased at the same time as floral notes, satin tannins and wine body augmented. Finally, the use of commercial mannoproteins improved some sensory characteristics of red wines related to positive astringency subqualities and aroma persistence. Highlights: Astringency subqualities of Aglianico and Sangiovese aged with commercial mannoproteins were evaluated. Body improvement, aroma revelation and odor complexity were obtained. Pigmented polymer formation was enhanced in the lower coloured wine. In the tannin-rich wine the main effect was on astringency characteristics. The effect of mannoproteins depended on wine and aging period.